Achievement motivation and academic performance - Wan Rafaei Abdul Rahman, (Universiti Kebangsaan Malaysia, 1973)
An attempt was made to relate achievement motivation to academic performance. Two scales for measuring achievement motivation i.e. Mehrabian Achievement Scale (MAS) and Russsell's Achievement Motivation Scale (RAMS) were administered to Malay students attending Basic Psychology course at one of the universities in Malaysia. The results indicated a positive significant correlation between the two scales and between MAS and course work in female subjects only. Course work was found to have positive correlation with final examination was also found between males and females. The differences in the results were discussed.